Charging for Agricultural Publications - William Wade (Journal of Applied Communications, 1981)
In an effort to determine policy and experience regarding cost-recovery for Cooperative Extension and experiment station publications, the University of California Agricultural Sciences Publications office surveyed other publications offices.